PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MENULIS CERPEN BERBASIS APLIKASI ANDROID - Dini Rahma Diani; Nurhayati Nurhayati; Didi Suhendi (Universitas Sebelas Maret, 2019)
This study aims to produce a valid,pratical and effective student worksheet (LKPD) based on Android applications for short writing material in Indonesia language learning. Development research was designed using research methods of modification and collaboration development theory proposed by Jolly Bolitho,Dick,Carey and Carey (2005). This LKPD frame work consists of the homepage menu, material, traning,assessment criteria, and development. To obtain information on the feasibility of the LKPD, expert validation was carried out covering aspects of material, language, and media feasibility. To test the practicality of LKPD, one on one and small group trials were conducted with data collection techniques through questionnaires. Finally, to find out the effective of LKPD field trials were carried out through experiments with data collection techniques using tests. Based on data analysis,it can be concluded that the LKPD writing short stories developed very valid is very practical and very effective as a learning facility for students. The resulting LKPD can be used as teaching materials to improve the quality of the process and learning out comes of writing short stories.